Regulatory Law and Regulatory Friction as FinTech Disenablers: Calibrating an EU Policy Response to the Adaptive Regulatory Sandbox in Member States - Ahern, Deirdre (My University, 2021)
With transformative evolution involving crypto-assets, machine learning applications and data-driven finance models, complex regulatory and policy issues are emerging. Inadequate frameworks in FinTech markets create regulatory friction and regulatory fragmentation. These limitations continue to feature when piecemeal regulatory transition occurs. The danger of EU Member States being left behind in the FinTech innovation race if the regulatory landscape is cumbersome or incomplete for new business models is real. Regulatory lag and regulatory friction also act as a ‘disenabler’ for ease of cross-border FinTech trade in the EU. This article critically engages with the manner in which the regulatory sandbox has rapidly gained critical mass in Member States as a valuable adaptive measure supporting a route to market for FinTech entrepreneurs. Against the backdrop of the European Commission’s Digital Finance Strategy, the article further advances scholarship on FinTech in the EU by probing the EU’s resulting regulatory dilemma, undertaking a systematic evaluation of the continuum of complex policy options available to the European Union in response to the spreading regulatory sandbox phenomenon.
PUBLISHED
Keywords: FinTech; Crowdfunding; Regulatory sandbox; EU financial services law; Digital finance; Initial coin offerings; Crypto-assets; Digital Engagement; Digital Humanities; International Integration; Smart & Sustainable Planet; Justice and safeguarding; Policy